Pengaruh Komitmen Organisasi dan Komunikasi Interpersonal terhadap Kinerja Karyawan dengan OCB Sebagai Variabel Intervening ( Studi Kasus pada Karyawan Plant Produksi PT Asia Pacific Fibers,Tbk Kendal) - Aldila Widya Pusparani; Sudharto Prawata Hadi (Universitas Diponegoro, 2018)
The performance of employees in production department PT Asia Pacific Fibers,Tbk still shows fluctuative numbers and many employees still get C score on their performance. This study aims to determine the effect of organizational commitment and interpersonal communication on the performance of employees with Organizational Citizenship Behavior (OCB) as an intervening variable in the employees of PT Asia Pacific Fibers Production Plant, Tbk Kendal. This type of research is explanatory research. The sample used is 92 respondents. The sampling technique used is random sampling with type of sample is proportional sampling. The data collection techniques used were questionnaires and literature study. Data analysis techniques are correlation test, coefficient of determination, simple linear regression test, multiple linear regression test, t and f significance test, path analysis and test of mediation effect of sobel with the help of program SPPS (Statistical Product and Service Solutions) version 23.0. Based on the analysis, it can be concluded that organizational commitment has a significant effect on employee’s performance and OCB, interpersonal communication has significant effect on performance and OCB, OCB has a significant effect on employee’s performance, and OCB is a mediating factor between organizational commitment and performance, but not a mediating factor between interpersonal communication and employee’s performance.The company sould be improve the factors that can increase organization’s commitment, interpersonal communication and organizational citizenship behaviour, such as improving the welfare of employees, make an open interpersonal communication, and to increase OCB, the employees must increase their self awareness.